Efficacy of dioctahedral smectite in infants with acute diarrhea: a double blind randomized controlled trial - A. A. Made Widiasa; Soetjiningsih Soetjiningsih; Putu Gede Karyana (Paediatrica Indonesiana, 2009)
Background  Acute  diarrhea  is  a sudden diarrhea which lasts lessthan  seven days  on  babies and children.  The  standard  treatmentby  WHO  in managing acute diarrhea  is  still  not  satisfactory forparents whose infants and children suffering from the disease.Dioctahedral  smectite  is  expected  to  decrease  the  volume,frequency, and duration  of  diarrhea.Objective  To  assess the clinical effects  of  dioctahedral smectite ininfants with acute diarrhea.Methods  A double-blind, randomized clinical controlled trial wasperformed on six to  12  months-old infants who were hospitalizedin Sanglah Hospital, Denpasar due to acute diarrhea .The subjectswere divided into two groups.  The  treatment  group was givenstandard  management  with  adjuvant  dioctahedral  smectitewhile  and  control group was given standard management withplacebo.Results  From  68  infants enrolled in this study, the  mean  durationof  diarrhea was significantly shorter in treatment group comparedto placebo group  [39.03  hours (SD  2.03)  vs  70.58  hours (SD3.78),  mean  difference  31.6 (95%  CI  22.90  to  40.19), P=0.001].The  RRR was  50%,  and  ARR  was  29%.  Kaplan-Meier survivalanalysis showed  that  duration  of  acute diarrhea was shorter intreatment  group  [36  hours (SD  1.7)  versus 72 hours (SD  4.18),mean difference  36.0 (95%  CI  21.81  to  50.19),  log rank test,P<0.0001].  In multivariate Cox regression analysis, it was foundthat  dioctahedral smectite influenced the duration  of  diarrheain infants with acute diarrhea  [OR  4.403 (95%  CI  2.39  to  8.12),P<O.OOOl].Conclusion  Dioctahedral smectite  can  shorten the duration  ofacute diarrhea.